Taxes as an Implementation of Pancasila Ideology in Counteracting the Negative Effects of Capitalism - Muhammad Abdur Rozaq; Jasran Asya; Eva Novita; Fraistifina Fraistifina; Yuwono Priyanto (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
Globalization and industrialization that link the ideas of capitalism are not under the ideology of Pancasila and Indonesia's national development is implemented based on economic democracy. The 1945 Constitution, Article 23A has established taxes as a source of funding for Indonesia's national development. The real threat of capitalism is environmental destruction and social inequality. This is necessary to counteract the negative effects of the influence of capitalism. This study aims to analyze the implementation of Pancasila ideology through the tax system to counteract the negative impact of the influence of capitalism. This research is legal and applies legal approaches and deductive analysis methods. The results showed that tax law contains legal certainty as a prevention of arbitrary practices and a form of democracy. The Tax Law contains benefits, by cooperating with every citizen to participate in the implementation of development through the payment of taxes. The Tax Law contains justice through the redistribution of income so that disadvantaged people can enjoy the same opportunities as those who are better able to achieve prosperity prospects.